MSC Differentiation: Osteogenic and Adipogenic Differentiation of Mesenchymal Stem Cells in Gelatin Solutions of Different Viscosities (Adv. Healthcare Mater. 23/2020). Issue 23 (2nd December 2020) - Lee, Kyubae; Chen, Yazhou; Yoshitomi, Toru; Kawazoe, Naoki; Yang, Yingnan; Chen, Guoping
Abstract : In article number 2000617 by Guoping Chen and co‐workers, a 3D biphasic gelatin solution/hydrogel system is used to investigate the influence of solution viscosity on balancing osteogenic and adipogenic differentiation of mesenchymal stem cells (MSCs). The differentiation of MSCs in gelatin solutions is dependent on their viscosities. High viscosity is beneficial for osteogenic differentiation while low viscosity for adipogenic differentiation.